Aerogel-based solar thermal receivers. (October 2017) - McEnaney, Kenneth; Weinstein, Lee; Kraemer, Daniel; Ghasemi, Hadi; Chen, Gang
Abstract: In any solar thermal application, such as solar space heating, solar hot water for domestic or industrial use, concentrating solar power, or solar air conditioning, a solar receiver converts incident sunlight into heat. In order to be efficient, the receiver must ideally absorb the entire solar spectrum while losing relatively little heat. Currently, state-of-the-art receivers utilize a vacuum gap above an absorbing surface to minimize the convection losses, and selective surfaces to reduce radiative losses. Here we investigate a receiver design that utilizes aerogels to suppress radiation losses, boosting the efficiency of solar thermal conversion. We predict that receivers using aerogels could be more efficient than vacuum-gap receivers over a wide range of operating temperatures and optical concentrations. Aerogel-based receivers also make possible new geometries that cannot be achieved with vacuum-gap receivers. Abstract : Graphical abstract: Abstract : Highlights: The equation of radiative transfer is used to model an aerogel solar receiver. Aerogel solar thermal receivers can outperform vacuum gap solar receivers. The Rosseland diffusion approximation works best for thin aerogels.